Faktor-faktor yang Memengaruhi Keberhasilan Usaha Mustahik pada Program Zakat Produktif di LAZ An-Nuur - Hardinata Muhammad; Deni Lubis; Dedi Budiman Hakim (Department of Islamic Economics, IPB University, 2018)
The high level of poverty in Indonesia becomes one of the problems that have not been successfully overcame by the government. Bogor Regency is the district with the poorest population in West Java Province in 2016. Many programs have been undertaken to overcome these problems by government of Bogor Regency. One of them is by optimizing the utilization of productive zakat conducted by Lembaga Amil Zakat (LAZ). LAZ An-Nuur established mustahik empowerment program by providing productive zakat in the form of financing for entrepreneurship. This study aims to analyze the factors that influence the success of a mustahik’s business in utilizing the productive zakat given by LAZ An-Nuur. The method used in this research is descriptive analysis and logistic regression analysis. Respondents in this study consisted of 48 beneficiaries of productive zakat funds. The results show that the factors that proved to influence the success of LAZ An-Nuur mustahik’s business are the age, length of business, business profits, and the frequency of financing.